Differences in short-term outcomes between open versus robot-assisted radical cystectomy in frail malnourished patients. Issue 7 (July 2020) - Palumbo, Carlotta; Knipper, Sophie; Pecoraro, Angela; Rosiello, Giuseppe; Luzzago, Stefano; Deuker, Marina; Tian, Zhe; Shariat, Shahrokh F.; Simeone, Claudio; Briganti, Alberto; Saad, Fred; Berruti, Alfredo; et al.
Abstract: Introduction: We tested whether frail patients may benefit from robot-assisted (RARC) relative to open radical cystectomy (ORC). Materials and methods: Frail patients treated with RC were identified within the National Inpatient Sample database (2008–2015). The effect of RARC vs. ORC was tested in five separate multivariable models predicting: complications, failure to rescue (FTR), in-hospital mortality, length of stay (LOS) and total hospital charges (THCs). As internal validity measure, analyses were repeated among non-frail patients. All models were weighted and adjusted for clustering, as well as all available patient and hospital characteristics. Results: Of 11, 578 RC patients, 3477 (30.0%) were frail. RARC was performed in 488 (14.0%) frail patients and 1386 (17.1%) non-frail patients. Among frail, RARC was only independently associated with shorter LOS (median 8 vs. 9 days, relative ratio [RR] 0.79, p < 0.001). Conversely, among non-frail, RARC was independently associated with lower complications (57.3 vs. 59.1%, odds ratio [OR] 0.82, p = 0.004) and shorter LOS (median 6 vs. 7 days, RR 0.88, p < 0.001), but also predicted higher THCs (+2850.3 US dollars, p = 0.001). Conclusions: In frail patients, the use of RARC did not result in better short-term outcomes except for one-day advantage in LOS. Conversely, in non-frail patients, the use of RARC resulted in lower complication rates and shorter LOS at the cost of higher THCs. In consequence, the benefit of RARC appears relatively marginal in frail patients and our data do not suggest a clear and clinically-meaningful benefit of RARC over ORC in frail radical cystectomy population.